cMIPS – a Pedagogical Tool for Studying Architecture - Hexsel, Roberto A.; Carmo, Renato (International Journal of Computer Architecture Education, 2013)
We present cMIPS, our VHDL implementation of the MIPS processor. Its use is proposed as an integrative platform for teaching Computer Architecture and related subjects. We show how the complete platform, which includes the processor and some simple peripherals, can facilitate the appropriation of the core concepts and their interrelationships. cMIPS is a model of the five-stage pipeline of the MIPS32 instruction set.